2022
DOI: 10.3390/ijms232012595
|View full text |Cite
|
Sign up to set email alerts
|

Asprosin in the Paraventricular Nucleus Induces Sympathetic Activation and Pressor Responses via cAMP-Dependent ROS Production

Abstract: Asprosin is a newly discovered adipokine that is involved in regulating metabolism. Sympathetic overactivity contributes to the pathogenesis of several cardiovascular diseases. The paraventricular nucleus (PVN) of the hypothalamus plays a crucial role in the regulation of sympathetic outflow and blood pressure. This study was designed to determine the roles and underlying mechanisms of asprosin in the PVN in regulating sympathetic outflow and blood pressure. Experiments were carried out in male adult SD rats u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…The expression of ROS and the level of inflammatory cytokines within PVN increased significantly in hypertension. PVN infusion with superoxide scavenger tempol and NADPH oxidase inhibitor can attenuate hypertension [ 42 , 43 ]. Our results showed that luteolin obviously decreased NAD(P)H-dependent ROS production in PVN, suggesting that luteolin can play its antioxidant role in the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of ROS and the level of inflammatory cytokines within PVN increased significantly in hypertension. PVN infusion with superoxide scavenger tempol and NADPH oxidase inhibitor can attenuate hypertension [ 42 , 43 ]. Our results showed that luteolin obviously decreased NAD(P)H-dependent ROS production in PVN, suggesting that luteolin can play its antioxidant role in the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…This signaling pathway may also be implicated in the cardiovascular-related effects of asprosin. Recently, high expression levels of asprosin mRNA and protein were detected in another hypothalamic nucleus known as paraventricular nucleus (PVN) ( 26 ). Interestingly, asprosin induced the sympathetic outflow in the PVN via activation of the cAMP–PKA signaling pathway mediated by NADPH oxidase activation and subsequent reactive oxygen species (ROS) production ( Figure 1 ) ( 26 ).…”
Section: Asprosin Receptorsmentioning
confidence: 99%
“…Recently, high expression levels of asprosin mRNA and protein were detected in another hypothalamic nucleus known as paraventricular nucleus (PVN) ( 26 ). Interestingly, asprosin induced the sympathetic outflow in the PVN via activation of the cAMP–PKA signaling pathway mediated by NADPH oxidase activation and subsequent reactive oxygen species (ROS) production ( Figure 1 ) ( 26 ). Microinjection of asprosin protein in PVN of adult Sprague-Dawley rats caused increasing levels of heart rate, mean arterial pressure, and renal sympathetic nerve activity in a dose-dependent manner ( 26 ).…”
Section: Asprosin Receptorsmentioning
confidence: 99%
See 2 more Smart Citations